Correlation between plasma levels of vitamin E and progesterone in sheep during pregnancy and after parturition - Aksakal, M; Naziroglu, M; Cay, M; Kalkan, C; Kaygusuzoglu, E; Cetin, H (Scientific Technical Research Council Turkey, 1997)
In this study, the levels of plasma vitamin E and progesterone and the correlation between them were investigated in shep during pregnancy and after parturition. Thirty Awasi sheep which have been fed on same diet and kept in same condition were used. For determination of vitamin E and progesterone, the blood plasma samples were obtained before and during pregnancy (Ist, 2nd, 3th, 4th, 5th months) and also after parturition. The level of Vitamin E was lower at the end of pregnancy than that in the first week after parturition. However, the levels of progesterone were found higher during pregancy compared to the value obtained after parturition. There were slightly but statistically insignificant negative correlation coefficients between plasma vitamin E and progesterone levels.
Koyunlarda Gebelik Süresince ve Do?um Sonrasi Kan Plazmasi E Vitamini ile Progesteron Hormonu Arasmdaki Ilişki
Keywords: vitamin E; progesterone; sheep; pregnancy